1996
DOI: 10.1109/59.535590
|View full text |Cite
|
Sign up to set email alerts
|

Load frequency control issues in power system operations after deregulation

Abstract: Open transmission access is a legal requirement in the United States, but is not fully implemented. Discussion of deregulation has so far focused principally on the tariff structure for transmission access, but operating the power system in this new environment will present significant problems of an almost purely technical nature. Something as simple as frequency control becomes challenging when implemented in the competitive, distributed control environment that true third party wheeling creates. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(98 citation statements)
references
References 3 publications
0
97
0
1
Order By: Relevance
“…Elgerd, 1970, Karnavas and Papadopoulos, 2002, Pan and Lian, 2005 while research work in deregulated AGC can be found in (Kumar et al, 1997, Delfino et al, 2002, Donde et al, 2001, Christie and Bose, 1996, Nobile et al, 2000, Bevrani et al, 2004, Karnavas, 2005, Shayeghi et al, 2006, Demiroren and Zeynelgil, 2007, Srinivasa et al, 2008. In the new restructured environment (see Figure 1), GenCos sell power to various DisCos at competitive prices.…”
Section: The Deregulated Market Environment For Agcmentioning
confidence: 99%
“…Elgerd, 1970, Karnavas and Papadopoulos, 2002, Pan and Lian, 2005 while research work in deregulated AGC can be found in (Kumar et al, 1997, Delfino et al, 2002, Donde et al, 2001, Christie and Bose, 1996, Nobile et al, 2000, Bevrani et al, 2004, Karnavas, 2005, Shayeghi et al, 2006, Demiroren and Zeynelgil, 2007, Srinivasa et al, 2008. In the new restructured environment (see Figure 1), GenCos sell power to various DisCos at competitive prices.…”
Section: The Deregulated Market Environment For Agcmentioning
confidence: 99%
“…Although it is conceptually clean to have separate functionalities for the GENCOs, TRANSCOs and DISCOs, in reality there will exist companies with combined or partial responsibilities. The LFC in a deregulated electricity market should be designed to consider different types of possible transactions, such as poolco-based transactions, bilateral transactions and a combination of these two [15]. In the new scenario, a DISCO can contract individually with a GENCO for acquiring the power and these transactions will be made under the supervision of ISO.…”
Section: Modeling Of a Two-area Thermal Reheat Interconnected Power Smentioning
confidence: 99%
“…According to [9] , by the end of 2008, there was 65 GW of wind power capacity (63.5 GW onshore and 1.5 GW offshore) installed in the EU -27, of which 63.9 GW was in the EU - 15. Among the EU countries, Germany and Spain continue to be Europe ' s leaders with total installed wind energy capacities of 24 GW and 17 GW, respectively where 63% of the EU ' s installed wind energy capacity is located in these two countries.…”
Section: Nuclear Power Plantsmentioning
confidence: 99%